Intraocular penetration of liposomal amphotericin B after intravenous injection in inflamed human eyes. Issue 9 (September 2021) - Ando, Tomoko; Kawakami, Hideaki; Mochizuki, Kiyofumi; Murata, Kazuhiro; Manabe, Yusuke; Takagi, Daisuke; Yagasaki, Ayaka; Niwa, Yoshiaki; Yamada, Noriaki; Ogura, Shinji; Matsumoto, Kana; Morita, Kunihiko; et al.
Abstract: Purpose: To determine the intraocular penetration of amphotericin B (AMPH-B) after an intravenously injection of liposomal amphotericin B (L-AMB) in inflamed human eyes. Methods: Seven eyes of 5 patients with fungal eye diseases (endophthalmitis in 6 eyes and keratitis in 1 eye) were treated with intravenous injections of 100–250 mg/day of L-AMB. Samples of blood, corneal button, aqueous humor, and vitreous humor were collected and assessed for AMPH-B. Results: The AMPH-B level in the cornea (604.0 μg/g) of the case with fungal keratitis exceeded the minimum inhibitory concentration. However, the levels in the aqueous and vitreous humors of the cases with fungal endophthalmitis were lower, e.g., 0.02 ± 0.01 μg/ml (0.09% of serum level) in the aqueous humor and 0.05 ± 0.08 μg/ml (0.17% of serum level) in the vitreous humor. Conclusions: The AMPH-B levels administered intravenously were very low in the aqueous and vitreous humors. Our findings indicate that intravenous L-AMB can be considered only for patients with mild endogenous fungal endophthalmitis, e.g., isolated chorioretinitis without vitreous extensions.